Leader-Member Exchange (Lmx), Organizational Justice (Oj), Mento Ring And Organizational Commitment (Oc): The Moderating Effect Of Sex - Leow, Kah Loong (2006)
The purpose of this study was to (a) examine the relationship of leader-member exchange (LMX), mentoring, and organizational justice on organizational commitment; (b) investigate whether sex moderates the above relationships and (c) test the interaction effects of LMX, mentoring, and organizational justice on organizational commitment. Specifically, the present study examines the relationship of four dimensions of LMX. namely- affect, contribution, professional respect, and loyalty; two dimensions of mentoring, namely- psychosocial and career: and three dimensions of organizational justice, namely - distributive, procedural, and interactional on each type of organizational commitment. Nine broadly hypothesized relationships were tested in a field study with a sample of 266 auditors serving in audit firms across Malaysia that are registered with the Malaysian Institute of Accountant (MIA). A total of 1100 questionnaires were posted out to MIA's firms located in the state of Penang. Selangor, and Wilayah Persekutuan. From the total of 318 completed questionnaires that were returned within a month (29% response rate), only 266 were usable (24.2% usable rate). The study setting was the work environment in the respective audit firms and participation was voluntary. The unit of analysis are the individual auditors who responded to the questionnaire. By and large. the results from hierarchical regression provided moderate support for the hypotheses.